Audience participation in theatre : aesthetics of the invitation - White, Gareth. 1968- (Houndmills, Basingstoke, Hampshire ; New York : Palgrave Macmillan, 2013)
"The popularity of participatory work with audiences is greater than ever, but the invitation to participate is rarely given attention as a feature of performance, or an important element of practice in its own right. This book presents a theory of audience participation in the theatre, based on the importance of the moment of invitation and how an event changes character when such an invitation is made. The materials from which theatre performance is made expand to include the audience participant's body and social being, with the participant's prior experience and expectations, and their embodied, affective response to the performance becoming of vital importance. Attending to this expanded set of performance media allows us to begin to articulate the aesthetics of participation, and thereafter to consider the ethics and politics of participation more precisely. "--
Machine generated contents note: -- Acknowledgements -- Introduction -- 1. Audience Participation -- 2. Why 'Aesthetics'? -- 3. The Practice and Theory of Audience Participation -- 4. Emancipating Spectators -- 5. Subjectivity as Material and Medium -- 6. The Structure of the Book -- PART I: PROCESS AND PROCEDURE -- 7. Antony Jackson and Frame Analysis -- 8. Goffman's Frame Analysis -- 9. The Frame Analysis of Audience Participation -- 10. Roles and Resources -- 11. Working Inside the Frame -- 12. Control and Social Structure -- 13. Horizons of Participation -- 14. The Aesthetic Meaning of Agency -- 15. Armadillo Theatre -- 16. Analysing Armadillo's Procedure -- PART II: RISK AND RATIONAL ACTION -- 17. Risk in Performance -- 18. Real and Perceived Risk -- 19. Actual Risk in Audience Participation -- 20. Horizons of Risk -- 21. Risk Management as Procedural Authorship -- 22. Ethical Issues in the Management of Real and Perceived Risk -- 23. Protecting Participants into Involvement -- 24. Reading the Audience Participant -- 25. Performativity and the Public Self -- 26. Know One's Fool -- PART III: IRRATIONAL INTERACTIONS -- 27. Emotion in Audience Participation -- 28. Embodied Cognition and the Enactive Theory of Mind -- 29. Empathy and Intersubjectivity in Audience Participation -- 30. Laughter -- 31. Crowds -- 32. Liminality and Communitas -- 33. Hypnosis -- 34. Procedural Authorship and Harnessing Intersubjectivity -- 35. De La Guarda's Liminoid Participation -- 36. Embodiment, Enculturation and Meaning -- PART IV: ACCEPTING THE INVITATION -- 37. Theatre Audiences and Feedback Loops -- 38. A New Horizon -- 39. Weather on the Horizon -- 40. Gaining Roles and Responsibilities -- 41. Experiential Learning -- 42. Reflexivity and Witnessing -- 43. Self-Awareness and Self-Forgetfulness -- 44. Autopoiesis, Allopoiesis, Heteropoiesis -- 45. Tim Crouch: The Author and I, Malvolio -- Conclusion -- 46. The Procedural Author -- 47. The Aesthetic Theory -- 48. Making Special -- 49. Patterning and Elaborating Participation -- 50. The Aesthetic Regime.
Includes bibliographical references (pages 214-220) and index.
Keywords: Participatory theater; Theater audiences; PERFORMING ARTS / Acting & Auditioning; PERFORMING ARTS / Theater / Direction & Production